(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes the fauna of the metallic noctuid moths (Lepidoptera: Noctuidae, Plusiinae) in the agroecosystems of the Fergana Valley. The metallic noctuid moths play a significant role in both natural and artificial communities of various zones of the Fergana Valley, and some of their representatives are pests in agroecosystems. As a result of the research, 3 species (Trichoplusia ni, Chrysodeixis chalcites, Macdunnoughia confusa) of the subfamily Plusiinae were noted for the first time in the agroecosystems of the study area. According to the conclusion of preliminary studies, the number of metallic noctuid moths (Plusiinae) species that have a trophic relationship with the studied agrocenoses of the Fergana Valley is 7.